Pengaruh Tuntutan Pekerjaan, Pengaturan Diri dan Stres Kerja terhadap Kinerja Karyawan dengan Kelelahan Kerja sebagai Variabel Mediasi: Studi pada Pt Bpr Tri Darma Putri di Kabupaten Klungkung - Ida Ayu Nila Dewi; I Gusti Bagus Honor Satrya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Employee performance is a critical determinant of organizational success. Increasing job demands, inadequate self-regulation, and work-related stress can influence employee performance and contribute to work fatigue. This study examines the effects of job demands, self-regulation, and work stress on employee performance, with work fatigue serving as a mediating variable at PT BPR Tri Darma Putri in Klungkung Regency. Grounded in the Job Demands–Resources (JD-R) framework, this quantitative study employed a saturation sampling technique involving 63 employees. Data were collected through surveys and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that job demands and work stress have a positive and significant effect on employee performance, indicating that these factors may encourage employees to achieve higher performance under certain conditions. In contrast, self-regulation does not directly affect employee performance. Work fatigue plays a mediating role in several relationships: it partially mediates the effect of job demands on performance, fully mediates the effect of self-regulation on performance, and does not mediate the relationship between work stress and performance. These findings highlight the importance of effectively managing workload, stress, and fatigue to maintain and improve employee performance.